2017
DOI: 10.1111/pace.13113
|View full text |Cite
|
Sign up to set email alerts
|

Procedural outcomes and long‐term survival following lead extraction in octogenarians

Abstract: At experienced centers, LE can be performed safely in octogenarians with procedural success rates and long-term survival comparable to younger individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
17
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 16 publications
7
17
1
Order By: Relevance
“…In our large single center analysis, the rate of clinical success was high, without significant differences between octogenarian and nonoctogenarian patients. This is in line with the literature, where a comparable success rate was found in patients treated with MD, 5 with laser extraction, 6 and with both techniques, irrespective of older age 14,15 . In the ELECTRA registry, age was not actually a predictor of clinical success 12 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our large single center analysis, the rate of clinical success was high, without significant differences between octogenarian and nonoctogenarian patients. This is in line with the literature, where a comparable success rate was found in patients treated with MD, 5 with laser extraction, 6 and with both techniques, irrespective of older age 14,15 . In the ELECTRA registry, age was not actually a predictor of clinical success 12 .…”
Section: Discussionsupporting
confidence: 88%
“…Fu et al did not find any correlation between the age on the patient and the rate of major complications 17 . And, finally, El‐Chami et al found no significant differences in survival up to 3 years following TLE in the over‐80s 14 …”
Section: Discussionmentioning
confidence: 98%
“…Lead removal is the most widely used procedure today in patients with complications related to cardiac electronic devices (pacemakers, implantable cardiac defibrillators and cardiac resynchronization therapy devices); however, TLE as a treatment method in the elderly still raises several questions. Age of the patient undergoing lead extraction is considered a risk factor for long-term mortality [12], although the evidence does not show an increased procedural risk in older subjects [4-9, 13]. Findings from this study corroborate previous research.…”
Section: Discussionsupporting
confidence: 80%
“…In a study of 235 patients (51 ≥80 years and 14 ≥90 years of age) undergoing TLE using laser energy there was a similar rate of major complications among octogenarians with a significantly lower BMI as compared with younger individuals (2.0 vs. 2.7%; p = 1.0) [5]. Analogically, a study of 774 patients (100 ≥80 years of age, including 9 ≥90 years of age) showed no differences in the occurrence of major complications (1.0 vs. 1.2%; p = 1.0) in elderly patients with a significantly lower body mass [4]. The current investigation did not confirm the effect of more comorbidities on the occurrence of major complications in the elderly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation